2012
DOI: 10.1056/nejmoa1107911
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi and Postural Stability in Patients with Parkinson's Disease

Abstract: Background Patients with Parkinson's disease have substantially impaired balance, leading to diminished functional ability and an increased risk of falling. Although exercise is routinely encouraged by health care providers, few programs have been proven effective. Methods We conducted a randomized, controlled trial to determine whether a tailored tai chi program could improve postural control in patients with idiopathic Parkinson's disease. We randomly assigned 195 patients with stage 1 to 4 disease on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
769
7
23

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 719 publications
(832 citation statements)
references
References 32 publications
14
769
7
23
Order By: Relevance
“…Current approaches to falls prevention in PD with exercise-based interventions have had conflicting outcomes when studied in clinical trials, with some evidence supporting Tai Chi. 4,5 Given the frequency of and morbidity associated with falls in PD, a pharmacological approach to falls prevention is an attractive prospect. Although dopaminergic depletion is the primary deficit and there is some evidence for improvement in gait variability with levodopa use, 6 falls remain common.…”
Section: Opinionmentioning
confidence: 99%
“…Current approaches to falls prevention in PD with exercise-based interventions have had conflicting outcomes when studied in clinical trials, with some evidence supporting Tai Chi. 4,5 Given the frequency of and morbidity associated with falls in PD, a pharmacological approach to falls prevention is an attractive prospect. Although dopaminergic depletion is the primary deficit and there is some evidence for improvement in gait variability with levodopa use, 6 falls remain common.…”
Section: Opinionmentioning
confidence: 99%
“…Their conclusion indicated that PD participant who takes Tai Chi lessons twice per week has significant improvements in the terms of gait, balance and functional mobility. Later, a research article was published in New England Journal of Medicine by Dr. Fu-Zhong Li [7], in which 195 patients with Parkinson's disease were randomly categorized into three groups; each group…”
Section: Introductionmentioning
confidence: 99%
“…The combination of motor and non-motor manifestations (e.g., depression, apathy and dementia) interferes with the individual's level of disability, and these factors negatively influence quality of life (QOL), which leads to isolation and low participation in social activities 6,7 . Distinct exercise modalities improve the symptoms of PD [8][9][10][11][12] . Exercise promotes plasticity of the central nervous system (CNS) 13 ; improves balance, gait, physical function and quality of life 8,9,14 , delays cognitive impairment 15,16 , dementia 17,18 , depression 19,20 ; and slows the progression of PD 21 .…”
Section: Introductionmentioning
confidence: 99%